Inhibition of Western-Diet Induced Hyperproliferation and Hyperplasia in Mouse Colon by Two Sources of Calcium - Richter, F. (Institutional Knowledge at Singapore Management University, 1995)
A simulation-based non-linear filter is developed for prediction and smoothing in non-linear and/or non-normal structural time-series models. Recursive algorithms of weighting functions are derived by applying Monte Carlo integration. Through Monte Carlo